1975
DOI: 10.1111/j.1432-1033.1975.tb04067.x
|View full text |Cite
|
Sign up to set email alerts
|

The Reconstitution of Escherichia coli DNA-Dependent RNA Polymerase from Its Isolated Subunits

Abstract: An improved method for the reconstitution of DNA-dependent RNA polymerase from its isolated subunits in the absence of urea is described. It allows the kinetic analysis of the assembly mechanism. The rate of reconstitution as well as the final yield are strongly temperature-dependent, whereas concentration has only a small effect. The kinetics of the formation of an intermediary complex a2p and an inactive enzyme complex a2pP'o were followed. The rate-limiting and temperature-sensitive step during reconstituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…It has been observed that a stable intermediary subassembly is formed during the genesis of RNA polymerase holoenzyme from its subunits. This subassembly consists of only two kinds of subunits with the stoichiometry x 2 B [2,3] and, like the complete enzyme, binds rifampicin [4-61. RNA, the product of transcription, can inhibit the binding of rifampicin to this subassembly [7].…”
mentioning
confidence: 99%
“…It has been observed that a stable intermediary subassembly is formed during the genesis of RNA polymerase holoenzyme from its subunits. This subassembly consists of only two kinds of subunits with the stoichiometry x 2 B [2,3] and, like the complete enzyme, binds rifampicin [4-61. RNA, the product of transcription, can inhibit the binding of rifampicin to this subassembly [7].…”
mentioning
confidence: 99%
“…The advantage of the T7 overexpression system (43) is that it allows massive production of transcriptionally poisonous 1 subunit without the risk that it would shut off its own synthesis. In combination with the in vitro RNAP reconstitution technology (15,31,39), this system will hopefully allow us to obtain RNAP molecules defective in essential functions.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation and reconstitution approaches, which have helped in elucidating the role of the components of bacterial RNA polymerases (Heil and Zillig, 1970;Palm et al, 1975;Ishihama and Ito, 1972), have not yet been worked out for the eukaryotic RNA polymerases. In summary, eukaryotic and eubacterial RNA polymerases are clearly distinguished by component patterns and functional characteristics such as promoter recognition sites, which would be expected for homologous molecules from different primary kingdoms.…”
Section: Nuclear Transcription In Eukaryotesmentioning
confidence: 99%